Advancing New Testament interpretation through spatio‐temporal analysis: Demonstrated by case studies. Issue 3 (29th April 2018) - van Altena, Vincent; Bakker, Henk; Stoter, Jantien
Abstract: This article explores, via three case studies, how spatio‐temporal analysis can advance New Testament text interpretation. Acts 2, verse 9 to 11 is the text of study. Case study 1 applies network analysis to data representing the Roman road network constrained by parameters valid for ancient times. This analysis provided new information on the background of people attending a festival in Jerusalem. Case study 2 located geographical entities from the text in a cartographic visualization and provided supportive information to compare contemporary textual resources. For the disciplines of textual and conjectural criticism (case study 3), spatio‐temporal analysis opens a new window to study what would be the most probable variant of the original text. The case study puts emendations that have been proposed over centuries in a 3D spatial context and provides in this way a sophisticated tool to relate different alternative variants of a specific text. From the case studies, it can be concluded that spatializing, visualizing, and spatially analyzing geographical concepts from the texts in Acts 2 contributes to the field of New Testament interpretation. Further work will elaborate on the findings.